A retrospective analysis of COVID-19 infection among healthcare workers of south east Assam, India - Dhar Chanda, Debadatta; Sen, Subhrendu Sekhar; Rajkhowa, Purnima; Choudhury, Basabdatta; Dey, Ajit; Upadhyay, Supriya (International Journal of Research in Medical Sciences, 2022)
Background: Health care workers (HCWs) are the frontline warriors, more prone to contracting coronavirus disease 2019 (COVID-19). They also have tremendous possibility of serving as transmission vectors to others. In India there is paucity of data on COVID-19 infection among HCWs. Therefore, it is important to evaluate the infection risk, clinical features, and source of infection, transmission and outcome in HCWs to safeguard them and to check further community spread. Methods: The aim of the study was to investigate the presence of COVID-19 infection among HCWs and to understand the risk factors for infection. Demographic and clinical data of HCWs declared SARS-COV-2 real time RT-PCR positive by VRDL, SMCH, Silchar during June 2020 to July 2021 was obtained from ICMR portal. Results: On data analysis it was found that during the study period a rate of 3.95% (316 out of 7997 cases) infection was among HCWs. Their mean age was 36 years. With maximum cases among male staffs (57.9%), and most common age group was young generation of 17-29 years. The peak acquisition of infection was in July 2020 during ATSP surveillance with 45.5% of infected HCWs. Of the infected HCWs majority were asymptomatic (74%) Although hospitalization rate was high i.e. 82.9% but severity was low with no mortality. Co-morbidity among infected cases was low 23.4%, usually in the aged group of ≥45 years. Doctors/PGTs and Nurses were the highly affected group. Conclusions: Safeguarding the HCWs from infection is the critical need for empowering the healthcare system and overcoming any pandemic in future as well.